Clinical and haemato-biochemical studies in natural trypanosomosis of equines - LAHA, R; BERA, A K; PANJA, P; SIKDAR, A (The Indian Journal of Animal Sciences, 2014)
During May 2002, equines (7) of Peoples for Animals, Calcutta, an Animal Shelter cum Hospital and Research Institute, Showed the clinical symptoms of intermittent fever (100.0F to 106.8 F), swelling of the dependent parts of the body, lacrimation, Staggering gait, weakness specially in hind quarters, reluctant for taking food and water, swelling of scrotum and lower abdomen and death of few animals. Microscopic examination of both Giemsa stained and wet blood smers form 6 out of 7 animals revealed the presence of Trypanosoma evansi. Haematological study of these animals indicated a decrease in haemoglobin, packed cell volume and total erythrocytic count with almost normal total leucocytic differential leucocytic counts. A concurrent decrease in serum glocose and albumin levels, normal total serum protein along with increased globulin and decrased albumin-globulin ratio, was also observed.